2020
DOI: 10.2196/15677
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Microscopy (IVM) in Human Solid Tumors: Novel Protocol to Examine Tumor-Associated Vessels

Abstract: Background Intravital microscopy (IVM) allows the real-time, direct visualization of microscopic blood vessels. This pilot clinical trial will elucidate the physical and functional characteristics of vessels associated with solid tumors. Objective The main objective of this study is to determine the feasibility of performing IVM in patients with solid tumors during the standard course of surgical resection. IVM will also be performed when vasopressors o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Patients were enrolled in single center, nonrandomized clinical trials at Mayo Clinic in Jacksonville, Florida, USA. These trials included Intravital Microscopy (IVM) in Patients with Peritoneal Carcinomatosis (ClinicalTrials.gov identifier: NCT03517852) and Intravital Microscopy in Human Solid Tumors (ClinicalTrials.gov identifier: NCT03823144) ( 6 , 8 ). Both trials received IRB approval from the Mayo Clinic (IRB #17-009823 and IRB #18-010370, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were enrolled in single center, nonrandomized clinical trials at Mayo Clinic in Jacksonville, Florida, USA. These trials included Intravital Microscopy (IVM) in Patients with Peritoneal Carcinomatosis (ClinicalTrials.gov identifier: NCT03517852) and Intravital Microscopy in Human Solid Tumors (ClinicalTrials.gov identifier: NCT03823144) ( 6 , 8 ). Both trials received IRB approval from the Mayo Clinic (IRB #17-009823 and IRB #18-010370, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Both trials received IRB approval from the Mayo Clinic (IRB #17-009823 and IRB #18-010370, respectively). The protocols for these trials, and the inclusion and exclusion criteria had previously been reported and are available through nct.gov ( 6 , 8 ). Briefly, patients underwent informed consent for participation and received a fluorescein skin prick test to evaluate the low risk of an allergic reaction to the fluorescein dye used to enhance the intravital in-human observations of blood vessels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation